(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article explores the international regulatory framework for green bond issuance—financial instruments designed to finance environmentally sustainable projects. The analysis focuses on key standards, including the Green Bond Principles, ICMA guidelines, and the taxonomies of the EU and other jurisdictions. Special attention is given to core requirements related to the use of proceeds, financial management, issuers’ internal procedures, and disclosure obligations. The paper examines current trends in legal development, the challenges of standardizing regulatory approaches, and issues concerning investor confidence. The study highlights the critical importance of harmonizing international standards as a foundation for the sustainable growth of the green finance market.